Discovering metformin-induced vitamin B12 deficiency in patients with type 2 diabetes in primary care. Issue 2 (20th February 2021) - Herbert, Laura; Ribar, Alicia; Mitchell, Sheryl; Phillips, Cynthia
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Background: Although metformin is the preferred initial pharmacological choice in type 2 diabetes, there is evidence that reveals a link between metformin use and vitamin B12 deficiency. The American Diabetes Association (ADA) has recently recommended periodic measurement of B12 levels for all patients on metformin. Local problem: Medical record data collected for the preintervention period showed that only 5% (n = 23) of patients diagnosed with diabetes and on metformin had B12 levels checked at an internal medicine primary care practice. Methods: This was a quasi-experimental project of preintervention and postintervention design using a checklist containing important measures of diabetes control. The project sample population consisted of data of adults with type 2 diabetes aged 18 years and older who were prescribed metformin in the previous year at the primary care practice. Interventions: The intervention focused on revising an existing diabetes measures checklist to include a prompt for an annual measurement of B12 levels. Results: There was significant improvement in monitoring vitamin B12 levels and discovery of low vitamin B12 levels. These data show that the number of B12 levels checked increased from 23 during the preintervention to 155 during the intervention ( p ≤ 0.0000). Conclusions: This project supports a conclusion that including a prompt to check B12 levels to an existing checklist increases B12 monitoring in this patient population. Results may encourage other providers to follow the ADA guidelines for monitoring vitamin B12 levels for patients taking metformin.